1981
DOI: 10.1536/ihj.22.739
|View full text |Cite
|
Sign up to set email alerts
|

Systolic time intervals in febrile states.

Abstract: SUMMARYSystolic time intervals (STI) were measured non-invasively in 12 controls and 10 cases each with fever due to acute malaria, acute viral infection, typhoid fever, and fever induced by T.A.B. vaccine. Apart from tachycardia, no clinical feature of impaired cardiovascular function was present in any of the febrile cases. Abnormalities of STI were found in all febrile groups. Of the total 40 cases, only 18 showed normal STI, 2 cases showed decreased PEP/LVET indicative of hyperdynamic circulatory state, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A decrease in cardiac function may occur in febrile illnesses, but whether myocardial damage is due to fever or the underlying infection is not known [166]. Weissinger et al found that in pigs with a bacterial infection with elevated body temperature, serum CK, lactate dehydrogenase (LD), and gamma-globulin (GG) levels were increased.…”
Section: Fevermentioning
confidence: 99%
“…A decrease in cardiac function may occur in febrile illnesses, but whether myocardial damage is due to fever or the underlying infection is not known [166]. Weissinger et al found that in pigs with a bacterial infection with elevated body temperature, serum CK, lactate dehydrogenase (LD), and gamma-globulin (GG) levels were increased.…”
Section: Fevermentioning
confidence: 99%
“…Eleven patients regularly receiving antipyretic drugs were excluded from the temperature study. This left 33 patients in the timolol group (mean (SD) age 65 (12) years) and 32 patients in the placebo group (mean (SD) age 63 (11)). There were 26 men and seven women in the timolol group and 29 men and three women in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…These results are not convincing evidence that there is myocardial depression in fever without hypotension. Abdullah et al (1981), reporting on a study of systolic time intervals in febrile patients (ten each with acute malaria, acute viral infection, typhoid and fever induced by TAB vaccine), showed a reduced PEP/LVET ratio in 11/40 cases; this was thought to represent subclinical myocardial impairment. Unfortunately there are no blood pressure data available in their paper so the results cannot be directly compared to those presented here.…”
Section: Discussionmentioning
confidence: 99%
“…We have not found any prolongation of the PEP/LVET ratio in our patients. The study of Abdullah et al (1981) was performed using a haemoglobin level of 7 g/100 ml as an exclusion criterion. The anaemia present in some of their subjects may have impaired their cardiac response to fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation